RE-IMAGINING MODEL GEREJA KONTEKSTUAL YANG LIBERATIF DI ASIA DENGAN INSPIRASI TEOLOGIS DARI CHOAN-SENG SONG DAN AHN BYUNG-MU - Harry Kristanto (P3TK, Sanata Dharma University, 2023)
At the same time as the sense of solidarity among Asian Churches is growing through Federation of Asian Bishop Conference (FABC), the effort to understand what it means to be a Church in Asia becomes more profound. We can mention several theological approaches which trying to reconstruct a distinctive face of the Asian Church, for example Choan-Seng Song who develops contextual theology with a transpositional mode. Starting from his critical position against the tendency of Western-centered nature of Christian theology, Song raised four important elements in a reorientation towards contextual theological exploration, namely vision, community, passion, and